Texts and Documents: New Challenges for TEI Interchange and Lessons from the Shelley-Godwin Archive - Trevor Muñoz; Raffaele Viglianti (Journal of the Text Encoding Initiative)
The introduction in 2011 of additional “document-focused” (as opposed to “text-focused”) elements represents a significant additional commitment to modeling two distinct ontologies for textual data within the standard governed by the Text Encoding Initiative (TEI) Guidelines. A brief review of projects using the new elements suggests that scholars generally treat the “document-focused” and “text-focused” models as distinct and even severable—the tools of separate interpretive communities within literary studies. This paper will describe challenges encountered by members of the development and editorial teams of the Shelley-Godwin Archive (S-GA) in attempting to produce TEI-encoded data (as well as an accompanying reading environment) that supports both document-focused and text-focused approaches through automated conversion. Based on the experience of the S-GA teams, the increase in expressiveness achieved through the addition of document-focused elements to the TEI standard also raises the stakes for “interchange” between and among data modeled according to these parallel approaches.